2007
DOI: 10.1016/j.jvs.2007.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking increases aortic dilatation without affecting matrix metalloproteinase-9 and -12 expression in a modified mouse model of aneurysm formation

Abstract: Aneurysm development in the elastase model is dependent on the quantity of active elastase infused. Exposure of animals to tobacco smoke after a relatively minor aortic elastase injury produces increases in elastin degradation and aneurysm size without affecting MMP-9 or MMP-12 expression. To our knowledge, this is the first demonstration in an animal model that smoking can act as a synergistic factor in AAA development. Further understanding of the relationship between smoking and AAA in this model may help u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…2 Exposure of animals to tobacco smoke after a relatively minor aortic elastase injury produces significantly more tissue inflammation and elastin degradation, demonstrating in the animal model that smoking can act as a synergistic factor in AAA development. 26 Results of our study confirms data that active cigarette smoking is associated with increased inflammation within the wall of AAAs and that neither former smoking nor packyears smoked were associated with increased aortic inflammation, suggesting an acute and not a cumulative effect. 15 A history of, or being treated for hypertension, or high plasma cholesterol concentrations showed no association with an increased aneurysm tissue inflammation in our study, in which 76.9% and 76% of patients were under antihypertensive medication and 61.5% and 50% of patients were under antilipidemic medication, in the low-and high-grade inflammation group, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…2 Exposure of animals to tobacco smoke after a relatively minor aortic elastase injury produces significantly more tissue inflammation and elastin degradation, demonstrating in the animal model that smoking can act as a synergistic factor in AAA development. 26 Results of our study confirms data that active cigarette smoking is associated with increased inflammation within the wall of AAAs and that neither former smoking nor packyears smoked were associated with increased aortic inflammation, suggesting an acute and not a cumulative effect. 15 A history of, or being treated for hypertension, or high plasma cholesterol concentrations showed no association with an increased aneurysm tissue inflammation in our study, in which 76.9% and 76% of patients were under antihypertensive medication and 61.5% and 50% of patients were under antilipidemic medication, in the low-and high-grade inflammation group, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…22 Other predisposing factors affecting menopausal age are late menarcheal age, BMI, parity, and heritability of menopausal age. 22,23 Neither smoking habits, a strong predictor for aneurysm development and growth, 24 nor menarcheal age, parity, and BMI differed significantly between the women with AAA Ͻ5 cm vs AAA Ն5 cm. These factors can consequently be excluded as alternative explanations for the lower menopausal age in women with AAA Ն5 cm.…”
Section: Discussionmentioning
confidence: 95%
“…Their expansion rate is enhanced by cigarette smoking. Lindholt et al followed up 117 patients affected by AAAs and found a correlation between cigarette smokers and an increase in the number of AAs [101]. Studies performed in animals confirmed this relationship, although the mechanism through which the cigarette smoking acts on the aortic wall is still unknown [102].…”
Section: Cigarette Smokingmentioning
confidence: 99%